CLINICAL PROFILE OF STROKE PATIENTS IN GOTONG ROYONG HOSPITAL - Supit, Paulus; Kurniawati, Nita; Kartikasari, Desy; Raymond Desun, Evander Aloysius; Erwin, Ferdinand (JOURNAL OF WIDYA MEDIKA JUNIOR, 2024)
Background: Stroke is a global health issue due to its high prevalence, mortality, and associated disabilities. The Global Burden of Disease Study identifies ischemic and hemorrhagic strokes as significant contributors to global health burdens. Understanding these factors in different populations is crucial for developing targeted interventions and improving patient outcomes.Methods: This retrospective descriptive study analyzed medical records of stroke patients at Gotong Royong Hospital from January to December 2023. Patients aged 18 years or older with acute stroke confirmed by CT or MRI were included.Results: Out of 224 stroke patients, 58% were male and 42% female. Most patients were over 70 years old (31.7%), with 29% aged 51-60 and 26.3% aged 61-70. Ischemic stroke was predominant (91.5%), while 8.5% had hemorrhagic stroke. Many patients (40.2%) arrived at the emergency department more than 24 hours after symptom onset. Hypertension was present in 68.8% of patients, diabetes in 36.6%, and dyslipidemia in 24.1%. The average length of stay was 4.13 days. Blood pressure measurements showed high prevalence of Grade 2 hypertension in systolic (37.05%) and prehypertension in diastolic (30.80%). Laboratory results revealed mean random blood glucose of 174.3 mg/dL, fasting blood glucose of 110.42 mg/dL, HbA1C of 8.06%, LDL cholesterol of 120.31 mg/dL, and triglycerides of 151.26 mg/dL.Conclusion: The majority of acute stroke patients at Gotong Royong Hospital are male, over 60, with ischemic stroke, and present more than 24 hours post-onset. These patients typically have a history of hypertension but no previous strokes, with an average hospital stay of 4 days. Many exhibit Grade 2 hypertension in systolic blood pressure and prehypertension in diastolic pressure. Understanding these profiles can guide better management and preventive strategies for stroke patients.